Salidroside attenuates LPS-induced inflammatory activation in young rats with acute lung injury via PI3K/Akt signaling pathway: Salidroside attenuates LPS-induced inflammatory activation - Du, Xinfang; Feng, Wenying; Zhang, Suhua; Lin, Xian; Song, Lihua; Shen, Na; Yang, Xiaoxiao (Cellular and Molecular Biology, 2023)
This experiment aimed to analyze the salidroside effect on lipopolysaccharide (LPS)-induced inflammatory activation in young rats with acute lung injury (ALI) via PI3K/Akt signaling pathway. In this study, sixty SD young rats were divided into 5 groups (control, model, salidroside low-dose, salidroside medium-dose and salidroside high-dose), with 12 rats in each group. ALI rat model was established. In the control and model group, rats were intraperitoneally injected with normal saline, while the salidroside low-, medium-, and high-dose groups were intraperitoneally injected with 5, 20, and 40 mg/kg salidroside, then the pathological changes of lung tissue, lung injury score, wet/dry lung weight ratio, neutrophils and TNF-α, MPO, MDA, NO, p-PI3K and p-AKT were detached and compared between these groups. Results showed that the ALI rat model was successfully established. The lung injury score, wet/dry lung weight ratio, neutrophils and TNF-α in alveolar lavage fluid, MPO, MDA, NO, p-PI3K and p-AKT in the lung tissue of the model group were increased than the control group. With the increase of salidroside dose, lung injury score, wet lung weight/dry lung weight ratio, neutrophils and TNF-α in alveolar lavage fluid, and the levels of MPO, MDA, NO, p-PI3K and p-AKT in lung tissues of the salidroside group were decreased then model group (P < 0.05). In conclusion, salidroside may reduce the activation of inflammatory cells in the lung tissue of young rats with LPS-induced ALI by activating PI3K/AKT signaling pathway, thereby exerting a certain protective effect on the lung tissue with LPS-induced ALI.